2015
DOI: 10.7874/jao.2015.19.3.144
|View full text |Cite
|
Sign up to set email alerts
|

Error Patterns Analysis of Hearing Aid and Cochlear Implant Users as a Function of Noise

Abstract: Background and ObjectivesNot all impaired listeners may have the same speech perception ability although they will have similar pure-tone threshold and configuration. For this reason, the present study analyzes error patterns in the hearing-impaired compared to normal hearing (NH) listeners as a function of signal-to-noise ratio (SNR).Subjects and MethodsForty-four adults participated: 10 listeners with NH, 20 hearing aids (HA) users and 14 cochlear implants (CI) users. The Korean standardized monosyllables we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…As expected, the number of errors increased in sentence recognition as either the SNR decreased or the rate of speech grew faster. Although the current results were supported by several previous studies, 17 , 18 , 20 they additionally showed a different pattern between the difficult conditions of background noise and time alteration. For instance, the data for background noise demonstrated that the SNHL groups’ speech recognition was significantly more vulnerable to interference from noise than the NHiA groups ( Figure 1 ).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…As expected, the number of errors increased in sentence recognition as either the SNR decreased or the rate of speech grew faster. Although the current results were supported by several previous studies, 17 , 18 , 20 they additionally showed a different pattern between the difficult conditions of background noise and time alteration. For instance, the data for background noise demonstrated that the SNHL groups’ speech recognition was significantly more vulnerable to interference from noise than the NHiA groups ( Figure 1 ).…”
Section: Discussionsupporting
confidence: 87%
“…The noun errors mainly consisted of no response and fail patterns in both the NHiA and SNHL groups, a trend that was magnified as either noise levels increased or speech grew faster. Chun et al 17 reported a similar pattern in a sample that did not include elderly subjects. Their adult group with normal hearing showed substitution errors dominantly regardless of the noise level, but hearing-impaired groups wearing hearing aids and/or having a cochlear implant had remarkable no response error types, rather than declined substitution errors.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The other method of assessment is to estimate incorrect answers or errors of speech perception and to analyze their patterns [ 5 ]. When conducted with monosyllabic words, for example, the error patterns of hearing aid (HA) and cochlear implant (CI) users were examined under quiet [ 6 ] and noise conditions [ 7 ]. The researchers found that the error patterns of substitution and no response showed much higher numbers than the other patterns, thus suggesting that auditory training could be applied to reduce the highest number of errors first of all-at first.…”
Section: Introductionmentioning
confidence: 99%